EXPRESSION OF FIGURATIVE MEANINGS IN KOREAN LANGUAGE - Baxranova Dilnoza Usmonkulovna (International Engineering Journal For Research & Development, 2022)
Polysemy is a phenomenon of language that needs to be studied both theoretically and practically. Its theoretical significance is reflected in the comparative study of the ways of semantic transfer in the work on the basis of bilingual materials. The practical aspect of the phenomenon of ambiguity can be seen in the structure of translation and explanatory dictionaries. Polysemy is examined in terms of the semantic structure of the word. The study of ambiguity in a particular language also focuses on the historical development, thinking, and cultural life of that people. The results can also be used effectively in the learning process.